Efektivitas Media Audio Visual dalam Pembelajaran PAI Daring di MTs Negeri 9 Yogyakarta - Munaya Ulil Ilmi; Muh. Alif Kurniawan (Institut Agama Islam Negeri Palopo, 2021)
The purpose of this study was to determine the effectiveness of learning using audio-visual media, especially in Islamic religious education subjects at MTs Negeri 9 Yogyakarta. This research is a quantitative descriptive research that uses a survey method. The data collection used is using a survey with a Likert scale. In analyzing the data, the researcher calculated the percentage in each of the existing indicators. The results of this study indicate that the effectiveness of using audio-visual media at MTs Negeri 9 Yogyakarta is included in the